Preterm children have unfavorable motor, cognitive, and functional performance when compared to term children of preschool age - Eliane F. Maggi; Lívia C. Magalhães; Alexandre F. Campos; Maria Cândida F. Bouzada (Brazilian Society of Pediatrics, 2014)
Objective: to compare the motor coordination, cognitive, and functional development of preterm and term children at the age of 4 years. Methods: this was a cross‐sectional study of 124 four‐year‐old children, distributed in two different groups, according to gestational age and birth weight, paired by gender, age, and socioeconomic level. All children were evaluated by the Movement Assessment Battery for Children - second edition (MABC‐2), the Pediatric Evaluation of Disability Inventory (PEDI), and the Columbia Mental Maturity Scale (CMMS). Results: preterm children had worse performance in all tests, and 29.1% of the preterm and 6.5% of term groups had scores on the MABC‐2 indicative of motor coordination disorder (p = 0.002). In the CMMS (p = 0.034), the median of the standardized score for the preterm group was 99.0 (± 13.75) and 103.0 (± 12.25) for the term group; on the PEDI, preterm children showed more limited skill repertoire (p = 0.001) and required more assistance from the caregiver (p = 0.010) than term children. Conclusion: this study reinforced the evidence that preterm children from different socioeconomic backgrounds are more likely to have motor, cognitive, and functional development impairment, detectable before school age, than their term peers.